Corporate social responsibility and hotel financial performance. Issue 2 (17th February 2022) - Babajee, Reena Bhattu; Seetanah, Boopen; Nunkoo, Robin; Gopy-Ramdhany, Narvada
ABSTRACT: This paper assesses the causal relationship between corporate social responsibility (CSR) activities and corporate financial performance using a sample of 43 hotels for the period 2007–2018. The research employs a dynamic panel vector autoregressive model (PVAR) which brings more analytical insights in the CSR- Financial Performance modeling. The results show that CSR has a positive and significant impact on corporate financial performance and lend support to the theoretical underpinnings with respect to the CSR and financial performance nexus. The results suggest that growth opportunities mediate the relationship between CSR and performance. High-growth hotels will have better opportunities to engage in CSR activities which in turn positively impact on their performance. Practically, our findings suggest that CSR is an important mechanism to improve the efficiency of organizations.